Investigating The Implementation of ICT In Education Reformation: National Instructor Teachers’ Perspectives - Thomas Wahyu Prabowo Mukti; Veronica Swanti; Mikael Dian Teguh (Universitas Jambi, Magister Program of English Education Department, 2020)
To facilitate quality teachers to support individual learning and encourage students to use technology, the Indonesian Ministry of Education has launched the National Instructor Teacher Program. Although the primary objective of the program is not limited to ICT, the instructor teachers’ existence is driven by the demand for technology use in classrooms. This qualitative paper aims to investigate National Instructor Teachers’ perspectives toward the use of ICT in education. Data were gathered by interviewing two National Instructor teachers from two provinces, namely Jawa Tengah and Yogyakarta. The results of this study showed that National Instructor teachers had a positive attitude towards the use of ICT. They were able to share and collaborate with other teachers and could find their own solutions related to the barriers in implementing ICT in their classes. The results of this study suggest that the government take a different approach in implementing the policy and support teachers forum to encourage ICT usage in the classroom and teachers’ autonomy.